2022
DOI: 10.1111/nuf.12760
|View full text |Cite
|
Sign up to set email alerts
|

Simulation: An active learning pedagogy for an undergraduate nursing leadership course

Abstract: Background Interpretive pedagogy with simulation encourages students to consider multiple perspectives contextually leading students to think deeper in a shared learning environment. Problem Clinical sites were lacking in a senior nursing leadership and management course and necessitated the adaptation of traditional clinical teaching methodologies. Approach Low‐fidelity simulation was used as an active learning strategy to fulfill clinical hours. Outcomes Comparing student groups' pretest mean scores were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…In addition, 13.5% of the participants expressed the wish to increase the time allocated to the "Master Class" training workshop. In this regard, studies have shown that simulation has the power to change the landscape of nursing practice and has many uses in nursing care [17,18]. New applications include basic and continuing education, nursing leadership, advanced practice, interprofessional education, and professional development [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 13.5% of the participants expressed the wish to increase the time allocated to the "Master Class" training workshop. In this regard, studies have shown that simulation has the power to change the landscape of nursing practice and has many uses in nursing care [17,18]. New applications include basic and continuing education, nursing leadership, advanced practice, interprofessional education, and professional development [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, studies have shown that simulation has the power to change the landscape of nursing practice and has many uses in nursing care [17,18]. New applications include basic and continuing education, nursing leadership, advanced practice, interprofessional education, and professional development [17][18][19]. Simulation has become an increasingly accepted practice in educational programs in clinical settings [18].…”
Section: Discussionmentioning
confidence: 99%